The dialect of Gammalsvenskby: compiling a dictionary of an unexplored language (slō — slǟp ˈǖt) - Alexander Mankov (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
The dialect of the village of Gammalsvenskby (Rus. Старошведское; current Ukrainian name Змiïвка) belongs historically to the Swedish dialects of Estonia, which were spoken before World War II in the Noarootsi peninsula (Sw. Nuckö), in the villages of Kurkse (Korkis) and Vihterpalu (Vippal), and in the islands of the Moonsund archipelago: Osmussaar (Odensholm), Vormsi (Ormsö), Hiiumaa (Dagö), as well as on the islands Suur- and Väike-Pakri (Stora och Lilla Rågöarna), Ruhnu (Runö), Naissaar (Nargö). In 1782, around 1,000 Swedes from the island of Dagö, which at the time belonged to the Russian Empire, were resettled in the Kherson Governorate. There, on the bank of the Dnieper River, a village that later came to be called Gammalsvenskby was founded. The native language of its founders was the dialect of Dagö. Up to end of the 2010s, some of the elderly residents of the present-day village preserved a language variety that goes back to the dialect of Dagö; this is the dialect of Gammalsvenskby. The present-day state of this dialect has not been systematically described in linguistic literature. The only source of data for this article is fieldwork with speakers of the dialect. The main objective is to present material recorded in the interviews in the most complete way possible and to describe the state of the vocabulary and inflection in the dialect. The entries include the following information: type of inflection; translation; phrases, sentences and short texts illustrating the usage (with initials of the informants). In many cases full paradigms are given as well. They include all phonetic and morphological forms that have occurred in the interviews.